Seismic strengthening of low-rise reinforced concrete frame structures with masonry infill walls: Shaking-table test. (15th June 2018) - Benavent-Climent, A.; Ramírez-Márquez, A.; Pujol, S.
Highlights: RC frames with infills are tested on a shaking table up to intolerable drifts. The system endured drift ratios close to 5% without signs of catastrophic failure. In the range of drifts between 1.7 and 5% the system described stable hysteretic loops. An equivalent diagonal single-strut infill model based on test results is proposed. Results open realm on possibilities of infills as a low-cost seismic retrofitting solution. Abstract: This study investigates experimentally the seismic behavior of reinforced concrete (RC) frames damaged by earthquakes and retrofitted with masonry infill walls. To this end, a 2/5 scale one-bay one story RC frame structure designed only for gravity loads (without seismic design consideration) was built in laboratory. Initially, it was subjected to several shakings to induce a moderate level of damage characterized by a maximum lateral drift ratio of 1.5% and a residual deformation of 0.12%. Next, the RC frame structure was retrofitted with two masonry infill walls oriented in the direction of motion and subjected to four uniaxial seismic simulations. The structure with infills experienced drift ratios of up to about 5% without signs of catastrophic collapse, and retained a reasonable energy dissipation capacity after the walls reached their maximum strength. The maximum drift reached was surprising given the brittleness of masonry. The results of the test open a realm of the possibilities for infill walls as a seismic retrofit solution. Finally, on the basis of experimental data acquired, a model for estimating the force-displacement relationship of the infills is proposed.